2017 25th European Signal Processing Conference (EUSIPCO) 2017
DOI: 10.23919/eusipco.2017.8081546
|View full text |Cite
|
Sign up to set email alerts
|

A new height-estimation method using FMCW radar Doppler beam sharpening

Abstract: Abstract-This paper presents a new method for estimating the height of extended objects using a Frequency Modulation Continuous Wave (FMCW) automotive radar. The proposed algorithm exploits the frequency shift caused by the Doppler effect while approaching stationary objects, to estimate target heights. Thus, the algorithm does not require multiple vertical antennas for height finding. First, the measured radial velocity is derived using sensor target geometry, then, a target height is formulated as a function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…the radar device. In principle, the radial velocity should be able to be computed by measuring the delay change over time [9,10].…”
Section: Preliminarymentioning
confidence: 99%
See 2 more Smart Citations
“…the radar device. In principle, the radial velocity should be able to be computed by measuring the delay change over time [9,10].…”
Section: Preliminarymentioning
confidence: 99%
“…It is found that the range and radial velocity of an object corresponds to the vertical and horizontal axis of the spectrum obtained by performing 2D FFT on a radar signal segment [9,10], which is usually referred to as the range-doppler spectrum. As shown for the ideal case in Fig.…”
Section: Preliminarymentioning
confidence: 99%
See 1 more Smart Citation
“…There are continuous advances made in this area of application, involving further improvement and adaptation of the DBS technique and applying super resolution methods for even greater refinement and image resolution [18][19][20]. The application of DBS for automotive purposes is less reported, there has, however, been research in the use of DBS for automotive height finding using 77 GHz frequency-modulated continuous-wave (FMCW) sensors [21]. This also introduces the use of the high-resolution spectral estimation technique called RELAX [22] to improve DBS resolution.…”
Section: Introductionmentioning
confidence: 99%
“…The first method uses a multi-path approach to exploit the height information by finding the difference in time delay between the line-of-sight (LoS) component of the signal, and the non-lineof-sight NLoS component [10]. The second method makes use of the Doppler signature of targets and is known as Doppler beam sharpening (DBS) [11], [12]. If the radar platform is moving, and the movement of the platform is known with a high enough precision, then the Doppler information for a target, combined with the azimuthal angular information, can be used to deduce the targets height from the ground.…”
mentioning
confidence: 99%